Labour force behaviour of elderly two adult households: Evidence from EU-countries - Matthias Deschryvere (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper studies the effect of individual and spousal characteristics on the labour force participation of elderly two-adult households. The comparative approach studies men and women separately and uses the first 8 waves (1994-2001) of the European Household Panel (ECHP). We compare results between three countries: Finland, a country with a high female labour force participation and Belgium and Germany, countries where female labour force participation is relatively low. Results of multinomial logit model estimations suggest that country differences are substantive and that men and women behave differently across different channels out of employment. We find evidence that the wife exerts a stronger influence on the husband's retirement decision. One explanation may be found in asymmetric complementarities of leisure: the husbands' enjoyment of nonemployment may depend much more on the wife also being non-employed than vice versa. There is evidence that the complementarities of leisure hypothesis dominates the added worker hypothesis. The results are in line with evidence from the U.S. and have some important implications: Simulations of the effect of changes in the pension system on men's retirement may yield incorrect answers if spill-over effects are ignored.
Keywords: 330; Ältere Arbeitskräfte; Erwerbstätigkeit; Altersgrenze; Geschlecht; Privater Haushalt; Finnland; Belgien; Deutschland